2011
DOI: 10.1016/j.jenvman.2011.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Limiting the impact of light pollution on human health, environment and stellar visibility

Abstract: Light pollution is one of the most rapidly increasing types of environmental degradation. Its levels have been growing exponentially over the natural nocturnal lighting levels provided by starlight and moonlight. To limit this pollution several effective practices have been defined: the use of shielding on lighting fixture to prevent direct upward light, particularly at low angles above the horizon; no over lighting, i.e. avoid using higher lighting levels than strictly needed for the task, constraining illumi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
357
1
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 480 publications
(372 citation statements)
references
References 36 publications
1
357
1
13
Order By: Relevance
“…Furthermore, considering that GABA is a target for therapeutic treatments of sleep disorders and the role of the SCN in sleep regulating processes, the seasonal influence on GABAergic function may affect the therapeutic manipulation of this neurotransmitter system differently in summer compared with winter. Together, these findings imply that some crucial neuronal networks within the CNS are sensitive to changes in day length, or even to prolonged artificial light exposure common in modern society (28,29).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, considering that GABA is a target for therapeutic treatments of sleep disorders and the role of the SCN in sleep regulating processes, the seasonal influence on GABAergic function may affect the therapeutic manipulation of this neurotransmitter system differently in summer compared with winter. Together, these findings imply that some crucial neuronal networks within the CNS are sensitive to changes in day length, or even to prolonged artificial light exposure common in modern society (28,29).…”
Section: Discussionmentioning
confidence: 86%
“…In developed countries, very few places can be considered free of light pollution (Cinzano et al 2000 ). If the consequences for activities such as stargazing are evident (Falchi et al 2011 ), the same cannot be stated for wild organisms and the ecological systems they are part of. However, the last decade has seen a boost of interest into the ecological consequences of light pollution Longcore 2006 ; Gaston et al 2013 ), which the symposium "Light in the darkness: how does artificial night lighting influence bird behavior and ecology?"…”
Section: Introductionmentioning
confidence: 99%
“…MLT suppression by ALAN has a dose-dependent response to both irradiance level and duration of the exposure [223]. Furthermore, the phase advance and suppression in MLT rhythms are intimately wavelength-dependent with more manifested effect at short wavelengths compared with long wavelengths [44,45,224]. Finally, the ALAN-induced MLT suppression is not age-related [225].…”
Section: Circadian Disruption Biomarkers In Obesity and Cancer Researchmentioning
confidence: 99%
“…The melanopsin-containing ipRGCs, which regulate the pineal MLT synthesis via the SCN, are extremely sensitive to short wavelength light exposure even at low irradiance [42] and for a short period [43] as they can suppress the synthesis of the pineal hormone MLT. The spectral sensitivity of MLT synthesis suppression demonstrates wavelength-dependent sensitivity with robust effects in response to short wavelength (450-500 nm) exposure [44,45]. Accordingly, a comprehensive study on the effect of various artificial lights on MLT suppression revealed that 4000 K and 5000 K LED lights were the most effective in the suppression of the hormone compared with counterpart technologies, such as incandescent, halogen, and florescent lightening systems [46].…”
Section: Circadian Disruptionmentioning
confidence: 99%